Anterior and Posterior Capsule- Periosteal sleeve avulsion as an unusual cause of Shoulder Instability - Eduvigis Aranda-Izquierdo; Olga Pérez-Moro; Marcos Fernández- Cuadros; Ana Maria Valverde-Villar; Alejandro Ortíz-Espada; Rafael Llopis-Miró (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
Traumatic anterior shoulder instability is a typical condition in young people and athletes. There are many different injuries that may be present, producing or coexisting with shoulder instability, in addition to classic Bankart lesion. Post-traumatic shoulder dislocation is much less common, between 2% to 5% of all shoulder dislocation, ascending to 10% on contact sports people. The most common causes are seizures, high energy trauma and electrocution. Traumatic multidirectional instability without hypermobility is extremely rare. We have found no reports in literature about a similar case. The purpose of this case report is to describe an unusual case of a patient who suffered an anterior and posterior shoulder dislocation simultaneously during self-defense training. Besides the complete description of a new and unusual type of injury, difficulty in diagnosis, surgical treatment and the used rehabilitation protocol are reviewed.